Ontological system processing of databases of scientific publications - Palagin, O.V.; Petrenko, N.G.; Boyko, M.O. (Проблеми програмування, 2022)
Development of theories, methods and algorithms for the discovery and formation of new knowledge always was one of the most important tasks for any researcher, especially if they actively working on creation of new scientific publications. There is no universal language to describe formally concepts (knowledge) and systemology of transdisciplinary scientific research. Because of this, researchers have a set of urgent problems, and one of them is the way of speeding up the process of finding information (in the form of cognitive-structure) in their own sources. Ontological system for processing of databases of scientific publications created to solve this problem for a researcher, who have from tens to hundreds of scientific papers published. We are unaware of search systems, which would provide the same information for a researcher in such a short time. Ontological system implements technologies of Information Retrieval and Knowledge Discovery in Databases with accent on technologies and instruments such as Semantic Web and cognitive graphics. Development of such ontological system have three stages. On the first stage instruments for system development created, methods and algorithms of interaction between system components "User ¾ Knowledge engineer ¾ Remote endpoint", also data added to the system at this stage. On the second stage task of multimedia presentation for conceptual and figurative structures, described in scientific documents, solved. Gaining new knowledge problem solved on the third stage. Розроблення теорій, методів й алгоритмів виявлення та формування нових знань завжди займало одне з центральних місць у будь-якого наукового співробітника, тим паче якщо він активно працює над створенням нових наукових публікацій. Відомо, що універсальної мови формального опису концептів (знань) та системології трансдисциплінарних наукових досліджень не існує. А тому перед науковцями стоїть ряд першочергових проблем, в тому числі проблема значного пришвидшення отримання науковим співробітником необхідної йому когнітивно-структурованої інформації із своїх джерел. Онтологічна система оброблення баз даних наукових публікацій саме так орієнтована на наукового співробітника, у якого в наявності опубліковано від декількох десятків до сотень наукових праць. Нам невідомі пошукові системи, які змогли б у максимально стислий термін надати науковому співробітнику таку інформацію. Онтологічна система реалізує технології Information Retrieval і Knowledge Discovery in Databases з акцентом на технології й інструментарій Semantic Web та когнітивної графіки. Розроблення такої онтологічної системи припускає три стадії: на першій стадії створюються інструментальні засоби реалізації системи, методики й алгоритми взаємодії системи «Користувач ¾ Інженер зі знань ¾ Віддалена прикінцева точка» та наповнення її даними; на другій стадії вирішуються задачі мультимедійного подання образно-понятійних структур, що описані в наукових документах; і на третій стадії – вирішення проблеми добування нових знань.